2007
DOI: 10.1104/pp.107.103762
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Constitutively Activated Plasma Membrane H+-ATPase Alters Plant Development and Increases Salt Tolerance

Abstract: The plasma membrane proton pump ATPase (H 1 -ATPase) plays a major role in the activation of ion and nutrient transport and has been suggested to be involved in several physiological processes, such as cell expansion and salt tolerance. Its activity is regulated by a C-terminal autoinhibitory domain that can be displaced by phosphorylation and the binding of regulatory 14-3-3 proteins, resulting in an activated enzyme. To better understand the physiological consequence of this activation, we have analyzed tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(111 citation statements)
references
References 69 publications
1
109
0
1
Order By: Relevance
“…The proton pump is the only means to recharge the system by converting the chemical energy of ATP to the PMF; thus, it is thought to play a fundamental role in diverse processes, including pathogen perception, hormone-mediated cell elongation, nutrient acquisition, root gravitropism, stomatal regulation, and salinity stress resistance (Michelet and Boutry, 1995;Schaller and Oecking, 1999;Palmgren, 2001;Hager, 2003;Fuglsang et al, 2007;Liu et al, 2009). Consistent with these predicted roles, mutant tobacco (Nicotiana tabacum) or Arabidopsis plants with altered H + -ATPase expression exhibit several phenotypes related to transport processes (Zhao et al, 2000;Vitart et al, 2001;Gévaudant et al, 2007).…”
mentioning
confidence: 67%
“…The proton pump is the only means to recharge the system by converting the chemical energy of ATP to the PMF; thus, it is thought to play a fundamental role in diverse processes, including pathogen perception, hormone-mediated cell elongation, nutrient acquisition, root gravitropism, stomatal regulation, and salinity stress resistance (Michelet and Boutry, 1995;Schaller and Oecking, 1999;Palmgren, 2001;Hager, 2003;Fuglsang et al, 2007;Liu et al, 2009). Consistent with these predicted roles, mutant tobacco (Nicotiana tabacum) or Arabidopsis plants with altered H + -ATPase expression exhibit several phenotypes related to transport processes (Zhao et al, 2000;Vitart et al, 2001;Gévaudant et al, 2007).…”
mentioning
confidence: 67%
“…Whereas wild-type pollen germination rate is enhanced by ;25% in the presence of fusicoccin, the germination rate of LAT52:NtAHA-GFP seems unaffected by the toxin ( Figure 6F). This result suggests that either the chimeric protein is already in an always-active state due to a structural modification of the autoinhibitory C terminus by the GFP fusion, such as what happens when the C terminus of these proteins is truncated (Gevaudant et al, 2007), or the GFP fusion is preventing pump activation via C-terminal phosphorylation and/or binding of 14-3-3 proteins (Palmgren, 2001), which would result in a chimeric pump with reduced or absent activity. It was shown that a similar H þ -ATPase-GFP fusion protein from N. plumbaginifolia (PMA4-GFP) was unable to complement a yeast mutant strain where the main plasma membrane H þ -ATPase was deleted (Lefebvre et al, 2004).…”
Section: Overexpression Of Nt Aha-gfp Affects the Physiological Regulmentioning
confidence: 96%
“…These H + -ATPases play regulatory roles in signal transduction, during cell expansion, turgor regulation, in the regulation of intracellular pH, and in the response of the plant to increases in soil salinity (Palmgren, 2001;Rober-Kleber et al, 2003;Fuglsang et al, 2007;Gevaudant et al, 2007;Merlot et al, 2007). A number of factors, including hormones (auxin and abscisic acid [ABA]), calcium, blue light, and fungal elicitors, have been shown to elicit changes in cellular pH through regulation of the PM H + -ATPase (Kinoshita et al, 1995;Xing et al, 1997;Kim et al, 2001;Brault et al, 2004;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%